Reliability-Based Analysis of Recycled Aggregate Concrete under Carbonation - Flora Faleschini; Mariano Angelo Zanini; Lorenzo Hofer (Advances in Civil Engineering)
Durability represents a crucial issue for evaluating safety and serviceability of reinforced concrete structures. Many studies have already focused on carbonation-induced corrosion of natural aggregate concrete (NAC) structures, leading to several prediction models to estimate carbonation depth. Less research is devoted instead on recycled aggregate concrete (RAC), about which limited experimental works exist aimed at assessing the carbonation coefficient in accelerated tests. Additionally, deteriorating processes are subject to uncertainty, when defining materials, geometry, and environmental actions during the service life of structures. This work presents a reliability-based analysis of carbonation resistance of RACs, using experimental carbonation coefficients derived from the literature, and applied in the full-probabilistic method prosed in fib Bulletin 34. Results demonstrate how aggregates replacement ratio and w/c ratio influence the reliability of RAC carbonation resistance.